SISTEM INFORMASI PEMANTAUAN PROSES BIMBINGAN TUGAS AKHIR MAHASISWA - Zulafwan Zulafwan; Willyansah Willyansah (J-Icon : Jurnal Komputer dan Informatika, 2020)
This study aims to build a system that will be used in supervising the guidance of students' final assignments. The final project is one of the courses in the higher education curriculum. However, the Final Project is in a very strategic position in terms of adequate quality of graduates. In the final project, students can show all the knowledge and abilities they have acquired during lectures and academic activities so far [1]. This application also functions as a progressive management, a web-based application because this application can also be used for inventory discussions because this feature is very useful. Not only that, Web-based applications can also work monitoring in the display system. Even the number of Web-Based Applications is now no longer available and can be ordered and tailored to the needs of consumers [2]. This application will be used as an additional menu on the main campus website. This system will later be used by students to input guidance progress. Lecturers use the system as a medium to study the development of each student's guidance. Meanwhile, the administrator has a role to input lecturer data, student data and final assignment title data